2011
DOI: 10.29311/ndtps.v0i7.461
|View full text |Cite
|
Sign up to set email alerts
|

The many positive impacts of participating in outreach activities on postgraduate students

Abstract: Postgraduate students are excellent role models for school students, where their passion and energy play a vital role in engaging younger students and spreading enthusiasm and excitement about science. However, participating in outreach is not a one way activity for these postgraduate students. Through focus groups we show that the postgraduate students perceive that there are many benefits for themselves. These benefits are identified and discussed. This paper also contrasts the postgraduate with their underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Graduate students rarely spend time interacting, teaching, or disseminating the results of their research with students or the non-academic community. However, it has been demonstrated that performing these activities improves their communication capacity, the ability to improve research design skills, manage unusual situations and questions, and enhances their confidence within their specialist area (Harrison et al 2011). These benefits also occur when carrying out outreach activities in a school group context.…”
Section: It Improves Graduate Students' Exper-mentioning
confidence: 99%
“…Graduate students rarely spend time interacting, teaching, or disseminating the results of their research with students or the non-academic community. However, it has been demonstrated that performing these activities improves their communication capacity, the ability to improve research design skills, manage unusual situations and questions, and enhances their confidence within their specialist area (Harrison et al 2011). These benefits also occur when carrying out outreach activities in a school group context.…”
Section: It Improves Graduate Students' Exper-mentioning
confidence: 99%
“…STEM (Science, Technology, Engineering, and Mathematics) departments run a variety of programs to promote their subject, disseminate current research, introduce school students to higher education, and support teachers and educators. STEM departments in higher education institutions are considering impacts on the institution, recruitment, those delivering the outreach, and society. There are many reasons, other than driving student recruitment, to support outreach including the following: building partnerships with local communities (e.g., schools), interest groups (e.g., local businesses, guiding/scouting groups), regional organizations (e.g., business, charities), national bodies (government, national organizations such as Learned Societies), and even international stakeholders (e.g., NASA), training of external and internal staff and students, knowledge exchange with an overarching objective to enhance the capacity of the institute. …”
Section: Introductionmentioning
confidence: 99%
“…To date there have been several investigations into the benefits of bringing research into schools in order to educate and encourage students to get involved in science from a young age [6][7][8], along with additional benefits for the researchers; in particular improved communication skills [9,10]. A number of projects have been set up to that effect, such as the US-based International Astronomical Search Collaboration [11] and the UK-based Institute for Research in Schools (IRiS) [12], which facilitates school students and teachers to participate in university-based STEM research projects.…”
Section: Introductionmentioning
confidence: 99%